No-drama discipline ebook The whole-brain way to calm the chaos and nurture your child's developing mind. - Siegel, Daniel J. (2014)
NEW YORK TIMES  BESTSELLER • The pioneering experts behind The Whole-Brain Child and The Yes Brain tackle the ultimate parenting challenge: discipline.   “A lot of fascinating insights . . . an eye-opener worth reading.”— Parents Highlighting the fascinating link between a child’s neurological development and the way a parent reacts to misbehavior, No-Drama Discipline provides an effective, compassionate road map for dealing with tantrums, tensions, and tears—without causing a scene.   Defining the true meaning of the “d” word (to instruct, not to shout or reprimand), the authors explain how to reach your child, redirect emotions, and turn a meltdown into an opportunity for growth. By doing so, the cycle of negative behavior (and punishment) is essentially brought to a halt, as problem solving becomes a win/win situation. Inside this sanity-saving guide you’ll discover   • strategies that help parents identify their own discipline philosophy—and master the best methods to communicate the lessons they are trying to impart • facts on child brain development—and what kind of discipline is most appropriate and constructive at all ages and stages • the way to calmly and lovingly connect with a child—no matter how extreme the behavior—while still setting clear and consistent limits • tips for navigating your child through a tantrum to achieve insight, empathy, and repair • twenty discipline mistakes even the best parents make—and how to stay focused on the principles of whole-brain parenting and discipline techniques   Complete with candid stories and playful illustrations that bring the authors’ suggestions to life, No-Drama Discipline shows you how to work with your child’s developing mind, peacefully resolve conflicts, and inspire happiness and strengthen resilience in everyone in the family. Praise for No-Drama Discipline   “With lucid, engaging prose accompanied by cartoon illustrations, Siegel and Bryson help parents teach and communicate more effectively.” — Publishers Weekly “Wow! This book grabbed me from the very first page and did not let go.” —Lawrence J. Cohen, Ph.D., author of The Opposite of Worry